Percepção de estudantes indígenas sobre as competências e habilidades adquiridas na Engenharia de Produção e seus impactos nas comunidades de origem - Gonçalves, Gilmara dos Santos (Universidade Federal de São Carlos, 2025)
With the growing presence of Indigenous students in higher education, there arises a need to investigate how these students have been developing their academic and professional competencies, especially in technically oriented programs such as Production Engineering. In this context, this study investigates the perceptions of Indigenous students enrolled in the Production Engineering course at the Federal University of São Carlos (UFSCar) regarding the competencies and skills developed throughout their undergraduate studies, as well as the potential impacts of this training process on their communities of origin. This qualitative research, conducted as a case study, involved seven students from the Sorocaba and São Carlos campuses through questionnaires and semi-structured interviews. The results reveal that, in addition to technical training, these students experience the university as a space for dialogue between academic knowledge and traditional wisdom. Areas such as logistics, sustainability, planning, and management were identified as particularly relevant to their community contexts. Despite the challenges faced, such as institutional adaptation and cultural conciliation, the participants recognize that they have been developing the competencies expected for the profile of a production engineer. The study concludes that affirmative policies and inclusive pedagogical practices contribute to the formation of professionals committed to social transformation.
Indigenous students' perception of the skills and competencies acquired in production engineering and their impact on their communities of origin
Keywords: Estudantes Indígenas; Ensino Superior; Engenharia de Produção; Competências; Comunidade; Formação acadêmica; Indigenous Students; Higher Education; Production Engineering; Competencies; Community; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO